2020
DOI: 10.21873/invivo.11850
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neutrophil-to-lymphocyte Ratio on the Effect of CRT for Patients With Rectal Cancer

Abstract: Background/Aim: Neutrophil-to-lymphocyte ratio (NLR) is an indicator of systemic inflammation and could be a predictive factor in malignant tumors. The aim of this study was to investigate the impact of NLR in patients with lower rectal cancer who received preoperative chemo-radiotherapy (CRT). Patients and Methods: Forty-eight patients with lower rectal cancer who underwent preoperative CRT and curative resection were enrolled. Blood samples were obtained before and after CRT. The relationship of NLR with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
0
24
1
Order By: Relevance
“…Therefore, it is possible to predict tumor response by NLR, PLR and MLR after CRT. Caputo and Ishikawa have suggested that NLR > 3.80 and 3.85 after CRT are predictors of poor tumor response (12,28). However, no relationship between hematological factors and tumor response after CRT was observed in our study, which may be related to the uncontrolled factors that affect the systemic in ammatory response in the case enrollment phase.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Therefore, it is possible to predict tumor response by NLR, PLR and MLR after CRT. Caputo and Ishikawa have suggested that NLR > 3.80 and 3.85 after CRT are predictors of poor tumor response (12,28). However, no relationship between hematological factors and tumor response after CRT was observed in our study, which may be related to the uncontrolled factors that affect the systemic in ammatory response in the case enrollment phase.…”
Section: Discussioncontrasting
confidence: 79%
“…Local and systemic in ammatory response is an important prognostic factor for colorectal cancer patients (10). In recent years, several studies have paid more attention on systemic in ammatory response indicators for predicting the prognosis of rectal cancer after CRT (11)(12)(13). In particular, neutrophil-lymphocyte-ratio (NLR), monocytelymphocyte-ratio (MLR) and platelet-lymphocyte-ratio (PLR) are considered as prognostic biomarkers for patients with rectal cancer (13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have demonstrated that various combinations of systemic inflammatory markers (e.g., serum C-reactive protein [CRP]), nutritional markers (total serum protein, serum albumin), and immune markers (neutrophil count, platelet count, and total lymphocyte count [TLC]), can be used to generate predictive indexes such as the lymphocyte to CRP ratio (LCR), neutrophil to lymphocyte ratio (NLR), prognostic nutritional index (PNI, based on serum albumin and TLC), CRP to albumin ratio, and Glasgow prognostic score (based on serum albumin and CRP) [ 4 13 ]. We previously reported that post-CRT NLR correlated with overall survival (OS) after surgery in patients with lower RC [ 9 ], highlighting the potential prognostic utility of such combination marker indexes.…”
Section: Introductionmentioning
confidence: 99%
“…Various combinations of blood test indicators have been studied in recent years as prognostic indicators for cancer patients, including the neutrophil/lymphocyte ratio (NLR) [3,4], Modi ed Glasgow Prognostic Score (mGPS) [5,6], and the Prognostic Nutrition Index (PNI) [7,8], among others. These combinations can represent systemic in ammation, immune function, and/or nutritional status.…”
Section: Introductionmentioning
confidence: 99%